Legal Culture and the Challenges of Ethical Enforcement: Legal Reform and Ethical Implications in the Advertising and Promotion of Healthcare Services in Indonesia - Sarwono, Aditya Pratama; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
The promotion of healthcare services, particularly in the field of dentistry, has rapidly evolved in the digital era. However, this development has not been accompanied by adequate legal regulations, leading to various ethical and legal concerns. This study aims to examine the effectiveness of healthcare advertising regulations in Indonesia, identify violations of medical ethical principles, and propose juridical solutions for fairer and more accountable law enforcement. The findings indicate that weaknesses in oversight, ambiguous legal norms, and poor inter-agency coordination are the primary obstacles to regulatory enforcement. Additionally, a permissive legal culture and excessive professional solidarity further undermine the implementation of the dental code of ethics. Many advertisements have been found to violate principles of honesty, justice, and non-maleficence, and often manipulate consumer perceptions. To address these issues, this study recommends comprehensive regulatory reform, the adoption of digital monitoring technologies, the strengthening of independent ethical bodies, and the protection of the dignity of dental professionals. Public education and cross-sector collaboration are also essential to building a more ethical, transparent, and responsible healthcare promotion system.